Neural dynamics underlying coordination between training-induced habitual and goal-directed responses. - He, Mengyang; Wen, Wen; Hazel, Douglas; Berning, Peyton (Cognitive, Affective & Behavioral Neuroscience, 2025)
Understanding the neurocognitive mechanisms that govern the coordination of habitual and goal-directed behaviors is important, because impaired coordination will cause various behavioral disorders. However, inducing habitual responses in human beings through repetitive stimuli-response training in a laboratory setting is a challenge. Well-trained sports athletes, who have automatic perception–action associations toward expertise-related stimuli, provide a natural sample to address this critical knowledge gap. We recorded electroencephalograms (EEG) of well-trained sports athletes while they performed a Simon task with expertise-related stimuli. By manipulating the congruency between the location of expertise-related stimuli and the response hand, we dissociated automatic habitual response and goal-directed inhibition control. We observed a stronger behavioral congruency effect on expertise-related stimuli than neutral stimuli in sports athletes but not healthy controls. Furthermore, sports athletes exhibited larger response-locked lateralized readiness potentials and stronger frontocentral beta band (15–25 Hz) activity in the congruent condition than the incongruent condition, which indicate an enhanced response tendency toward expertise-related stimuli. In contrast, prominent mid-frontal theta (3–7 Hz) activity observed in the incongruent condition signaled the involvement of response inhibition. Additionally, lateralized readiness potentials amplitude and theta power showed significant correlation with performance efficiency. Taken together, these results suggest that sports athletes exhibit an enhanced coordination for expertise-related stimuli, involving automatic response preparation and proficient response inhibition through extensive training.